Kolaborasi Zoom dengan WAG Sebagai Potret Merdeka Belajar pada Masa New Normal di SMK Negeri 4 Gowa - Zaenab Zaenab (Jurnal Paedagogy, 2021)
This study aimed to describing the portrait of freedom of learning through Zoom collaboration with the WA Group in the New Normal era in class X TKJ 1 SMK Negeri 4 Gowa. This research method used descriptive methods with a qualitative approach. The subjects of this study were students totaling 35 people. The research instrument used observation, tests, and questionnaires. Meanwhile, the data analysis technique used in this research was descriptive analysis. The results of this study indicate that the motivation and learning activities of class X TKJ 1 SMK Negeri 4 Gowa students during the new Normal period with the learning process through the collaboration of Zoom with the WA Group are in a positive tendency with a percentage agreeing 41.5% and those who quite agree 42.0 %. From this data it can be concluded that Zoom's collaboration with the WA Group as a portrait of independent learning is the best solution as an alternative method of learning during the Covid-19 pandemic.